1994
DOI: 10.1007/bf02548484
|View full text |Cite
|
Sign up to set email alerts
|

Group therapy with adolescents who have learning disabilities and social/emotional problems

Abstract: This paper presents groltp therapy with adolescents who have learning disabilities and sociallemotional problents. First, the paper reviews the literature on prychosocial development ancl interventions offered to these adolescents. Thire is agreement in the literature that group therapy is beneficial for adolescents. I.earning disubled uclolescents meet the criteria Jbr receiving this intervention. Despite this, review of the literature sulgests that this population is not generally offered group therapy. Twct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…There is literature on the benefits of group treatment for this population, which notes that modifications may be required to address the members' communication difficulties (Brown and Papagno, 1991;Coché and Fisher, 1989;Mishna, 1996aMishna, , 1996bMishna, Kaiman, Little, and Tarshis, 1994;Pickar, 1988).…”
Section: Group Treatment For Children and Adolescents With Learning Dmentioning
confidence: 99%
See 2 more Smart Citations
“…There is literature on the benefits of group treatment for this population, which notes that modifications may be required to address the members' communication difficulties (Brown and Papagno, 1991;Coché and Fisher, 1989;Mishna, 1996aMishna, , 1996bMishna, Kaiman, Little, and Tarshis, 1994;Pickar, 1988).…”
Section: Group Treatment For Children and Adolescents With Learning Dmentioning
confidence: 99%
“…One agency specialized in work with children and youth who have LD, and utilized a group treatment approach that emphasized interpersonal treatment, mutual aid and adaptations to the LD (Mishna, 1996a(Mishna, , 1996bMishna et al, 1994;Yalom, 1995). The other agency worked with "high-risk, hard-to-serve" youth and primarily used CBT in group work.…”
Section: Group In Collaborative Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, knowing when and if to include carers or supports can be a challenge. Mishna et al (1994) and Mishna and Muskat (2004) found that many youth with disabilities had experienced psychosocial losses with their barriers to connect with peers in a social environment. In their studies, the authors found that psychodynamic groups could be used to correct psychosocial losses experienced by adolescents with disabilities.…”
Section: Reiterated the Findings Of Cowls Andmentioning
confidence: 99%
“…In their studies, the authors found that psychodynamic groups could be used to correct psychosocial losses experienced by adolescents with disabilities. Psychodynamic groups benefited group members as they experienced feelings of acceptance and safety among peers, empathy and caring for others, and a supportive environment through group therapy (Mishna et al, 1994;Mishna, 1996;Mishna & Muskta, 2004). Longhurst et al…”
Section: Reiterated the Findings Of Cowls Andmentioning
confidence: 99%